The Influence of Social Representations on Attitude, Behaviour, and Adaptation Strategies on Perceptions about Climate Change in the Fiji Islands: A Review of Literature - Aisea Rainima; Rizka Halida (G-Couns: Jurnal Bimbingan dan Konseling, 2024)
Social Representation Theory (SRT) is a successful framework that has been used for many years to understand how individuals and groups construct, communicate, and navigate their social reality. Using a narrative method of literature review, this study, with synthesis of findings from previous research, examines how social representations influences attitudes, behaviours, and adaptation strategies related to perceptions about climate change in the Fiji Islands and the Pacific. Findings from the synthesis of results highlights the importance of considering local beliefs and cultural contexts in shaping responses to climate change. The discoveries also place emphasis on the critical role of beliefs and perceptions in driving adaptation efforts and community resilience. For future research, there is a need for inclusive approaches that put together local knowledge and perspectives into climate change policies and strategies that encourages sustainable solutions in Fiji, the Pacific Islands and beyond. Keywords: social representation, climate change, fiji islands, adaptation strategies, community perceptions